THE INFLUENCE OF LEADERSHIP IN IMPROVING PERSONNEL PERFORMANCE AT TRADITIONAL ISLAMIC BOARDING SCHOOL (DAYAH) - Usman, Nasir; AR, Murniati; Marzuki, Marzuki (Jurnal Ilmiah Peuradeun, 2016)
This study aims at determining styles of leadership in improving the performance of personnel, factors affecting the personnel performance, and inhibitors in improving the performance of personnel. This study used a qualitative approach with descriptive methods. Data collection techniques were done through observation, interview and documentation study. The subjects were principal, vice director, heads of division, and teachers of Dayah. The results showed that: 1) The leadership styles of dayah in improving the performance of personnel was a consultative, participative and instructive leadership style. 2) Factors that affected performance of personnel were the authority and charismatic of the principal in the presence of personnel, and democratic in decision making, and the religious environment, 3) The limiting factors in improving the performance of the personnel were the number of students that exceeds the capacity dormitories which were available, some of the personnel did not have the administration skill background, the minority of personnel who were less active, and were not able to provide financial support for the personnel.